SECONDARY PROFESSIONAL EDUCATION IN UNIVERSITY COMPLEX: ENVIRONMENTAL ASPECT - Viktoria A. Pulkina; Nataliya E. Shulepova (Moscow Polytechnic University, 2016)
The article dwells on the process of formation of a united educational space of a University complex on the example of three Ukhta colleges accession to the Ukhta State Technical University. Special attention is paid to adaptation of Ukhta Forestry College personnel to the University complex. This year this college has celebrated its 85th anniversary.